DASHBOARD TINGKAT KEPUASAN DAN PENJUALAN CV. PLUS LESTARI RAYKAT - Johan Tjung; Hugeng; Tri Sutrisno (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
Dashboard is a tool used to serve information in a visual or graphical indicator model that summarizes information to make it easier to understand. The purpose of this thesis is to create a dashboard application that can be used to measure the level of satisfaction and sales performance on CV. Plus Lestari Rakyat. The method used is Extract, Transform, Load (ETL) and Prototyping namely by listening to all kinds of input provided by users. The ETL method imports data into SQL SERVER and then converts it into master data which is easier to process into fact table data and is ready to become a master database. The result of making this dashboard is to assist users in analyzing and monitoring the level of satisfaction and sales at the company.